Perception of electronic medical records (EMRs) by nursing staff in a teaching hospital in India - Naveen Kumar Pera; Amrit Kaur; Raveendra Rao (International Journal of Advanced Medical and Health Research, 2014)
Background: Currently, in India, many healthcare organizations and their managements appreciate the advantages of electronic medical records, but they often use them. The current push for universal health coverage in India with National Rural Health Mission (NRHM) and National Urban Health Mission (NUHM) helping toward healthcare reforms highlights the importance of implementing information technology as a means of cutting costs and improving efficiency in healthcare field. The quality of documentation of patient care rendered at healthcare destinations is very important to showcase the growing stature of healthcare in India. Aims: As maintaining the medical records is very important, storage and retrieval of the information is also important for future patient care. In this regard, implementation of electronic medical records in hospitals is essential. Through this study, we wanted to highlight the perceptions of healthcare personnel, who are in the core team of delivering healthcare, toward implementation of electronic medical records. Methods: A cross-sectional study was carried out among doctors (post-graduates) and staff nurses. The sample size for post-graduate students and nurses was 164 and 296, respectively, in this study. The study was carried out during the period from January to June 2013, and a survey was conducted with the help of a validated, pre-tested questionnaire in a tertiary care medical college hospital in India. Results: The results showed that 75% of the study population are comfortable working with electronic medical records. They mentioned that display of diagnosis, medications, and allergies of patients on the records was most important. Their perception was that electronic medical records improve timely decision-making and patient care due to immediate access to the patient′s disease history. Conclusion: The major problems faced by nurses, as per our study, are delay in services due to dispersion of records, multiplicity of form types consuming major time, and inability to understand doctors′ notes.